Efektivitas Edukasi Audio Visual terhadap Peningkatan Pengetahuan dan Sikap Remaja Putri tentang Gizi Seimbang “Isi Piringku” - Musdalipa Musdalipa; Fenti Putri Cahyani; Kristina Paskana; Nora Veronica; Lety Arlenti; Herianti Herianti (Universitas Malahayati Lampung, 2026)
ABSTRACT Young women are the early period of contribution to intergenerational quality. Where adolescent girls with nutritional problems such as anemia, obesity and chronic energy deficiency (SEZ), if the adolescent girl is pregnant, the risk of giving birth to a baby with low birth weight (BBLR) and stunting, premature birth, and maternal and child mortality during childbirth is higher. One of the efforts that can be made through balanced nutrition health education. Education in this case is part of nutrition education as an effort to bring about changes in knowledge and attitudes in terms of consuming balanced nutritional foods in the visual of Isi Piringku. The visual of Fill My Plate depicts a healthy eating guide with 50% vegetables and the other 50% in the form of staples and side dishes. The use of audio-visual media in providing education because it is considered interesting and not noticeable by displaying movements, images and sounds. The purpose of this study was to determine the influence of audio visual intervention on the knowledge and attitudes of adolescent girls about balanced nutrition